2021
DOI: 10.1007/s10903-021-01254-z
|View full text |Cite
|
Sign up to set email alerts
|

Immigration Policy Vulnerability Linked to Adverse Mental Health Among Latino Day Laborers

Abstract: Latino day laborers in the United States are socially and economically vulnerable due to exclusionary immigration policies. Using data from a multi-mode survey, we examine the relationship between immigration policy legal vulnerability and mental health outcomes among 138 Latino, male day laborers (mean age = 45.65, SD = 12.05). Multivariable linear and logistic regression models separately estimated the effect of legal vulnerability, as measured by the Perceived Immigration Policy Effects Scale, on anxiety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Though unlikely, there is the possibility that Latinx parents contending with pandemic stress, increased policy vulnerability, and anxiety and depressive symptoms were more likely to participate in the study, making these associations spurious. However, previous studies have found that perceived immigration policy vulnerability and pandemic stress are independently associated with increased depressive and anxiety symptoms among undocumented populations (Haro-Ramos & Rodriguez, 2022;Serafini et al, 2021;Velarde Pierce et al, 2021), which increases confidence in our findings. Although we assessed participants past-month and past-2-week symptoms, we cannot entirely exclude the possibility of recall bias.…”
Section: Limitations and Strengthssupporting
confidence: 76%
“…Though unlikely, there is the possibility that Latinx parents contending with pandemic stress, increased policy vulnerability, and anxiety and depressive symptoms were more likely to participate in the study, making these associations spurious. However, previous studies have found that perceived immigration policy vulnerability and pandemic stress are independently associated with increased depressive and anxiety symptoms among undocumented populations (Haro-Ramos & Rodriguez, 2022;Serafini et al, 2021;Velarde Pierce et al, 2021), which increases confidence in our findings. Although we assessed participants past-month and past-2-week symptoms, we cannot entirely exclude the possibility of recall bias.…”
Section: Limitations and Strengthssupporting
confidence: 76%
“…Quantitatively, increased odds or frequency of depression or depressive symptoms were reported in six included articles. Populations who reported these internalizing symptoms included Latinx adults awaiting deportation proceedings (Bailey et al., 2021), Latinx children with higher levels of mistrust of others in their community (Cross et al., 2020), male Latinx day laborers with higher levels of legal vulnerability (Haro‐Ramos & Rodriguez, 2021), Latinx adolescents and adults with a close social tie who had been deported (Pinedo & Valdez., 2020; Roche et al., 2020), and sexual minorities who are also ethnic minorities (Krueger et al., 2021). Depressive outcomes were thus pervasive across age groups within the Latinx community during the Trump administration.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, 52% of all negative emotions related to immigration in this sample were fear‐based (Wray‐Lake et al., 2018). Of the three quantitative articles reporting anxiety levels, populations included Latinx adults in deportation proceedings (Bailey et al., 2021), male Latinx day laborers with higher levels of legal vulnerability (Haro‐Ramos & Rodriguez, 2021), and Latinx adults with a close social tie who had been deported (Pinedo & Valdez., 2020). Of the 21 included articles, only two articles discussed somatic symptoms and internalizing symptoms broadly and their associations with a generalized stress response to immigration actions/news (Bailey et al., 2021; West et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations